Do Quality of Financial Reporting and Tax Incentives Effect on Corporate Investment Efficiency with Good Corporate Governance as Moderating Variables? - Sitorus, Riris Rotua; Murwaningsari, Etty (Journal of Accounting, Business and Finance Research, 2019)
This study aims to analyze the effect of Quality of Financial Reporting and Tax Incentives on Corporate Investment Efficiency with Good Corporate Governance as a Moderating Variable. The sampling method that used was purposive sampling method. The independent variables are Quality of Financial Reporting and Tax Incentives. Then the dependent variable is Corporate Investment Efficiency. The moderating variable is Good Corporate Governance. The population in this study are manufacturing companies which are listed on the Indonesian Stock Exchange as long as in 2013-2017. The results of the study showed that the Quality of Financial Reporting and Tax Incentives did not effect the Corporate Investment Efficiency. Good Corporate Governance has a negative effect on Corporate Investment Efficiency. Good Corporate Governance is able to strengthen the influence of Quality of Financial Reporting on Corporate Investment Efficiency. Furthermore, Good Corporate Governance is not able to strengthen the Influence of Tax Incentives on Corporate Investment Efficiency.